Zimmet Suçları - Topal, Erman (My University, 2008)
Debit Crimes are analyzed under 3 sections in this working. In first section with “General Knowledges” caption, “State and Statecraft”, “Public Administration” and “Public Servant” notions are explained and in second section, it is firstly told about “Debit”, ”Historical Changes of Debit Crime”, “ Legal Values prevented in arrangement of Debit Crimes by law setter”,”Elements of Debit Crimes and special appearance types of it” notions. In third section, it is told about reasons affecting Debit Crime, Debit Crimes, prosecution method of it,commissioned court for it, sanction of it arranged in Banks’ Law, other parallel characteristic crimes arranged in penal code and their differences. After introduction for Debit Crime, Debit Crime arranged on i.247/ 1 and Debit Crime arranged on i.247/ 2 are analyzed in same section, but under different captions then congruity reasons to law, active regret rules,sanctions,reasons increasing penalty that is able to be accepted for both crimes, investigation and prosecution of these crimes,differences from other crimes are analyzed.In conclusion section,This working is tried to evaluate in a whole.
Keywords: Kamu Görevlileri; Zimmet Suçu; Zimmete Para Geçirme